Robbins basic pathology - Vinay Kumar MBBS MD FRCPath (Editor); Abbas, Abul K.; Aster, Jon C.; Perkins, James A. (Philadelphia, Pennsylvania : Elsevier, 2018)
"This thoroughly revised edition continues with a strong emphasis on pathogenesis and the clinical features of disease, adding new artwork and more schematic diagrams to further aid in summarizing key pathologic processes and expand the already impressive illustration program"--
The cell as a unit of health and disease / Richard. N. Mitchell -- Cell injury, cell death, and adaptations -- Inflammation and repair -- Hemodynamic disorders, thromboembolism, and shock -- Diseases of the immune system -- Neoplasia -- Genetic and pediatric diseases / Anirban Maitra -- Environmental and nutritional diseases -- General pathology of infectious diseases / Alexander J. McAdam, Karen M. Frank -- Blood vessels / Richard N. Mitchell -- Heart / Richard N. Mitchell -- Hematopoietic and lymphoid systems -- Lung / Aliya Noor Husain -- Kidney and its collecting system / Anthony Chang, Zoltan Laszik -- Oral cavity and gastrointestinal tract / Jerrold R. Turner, Mark W. Lingen -- Liver and gallbladder / Neil D. Theise -- Pancreas / Anirban Maitra -- Male genital system and lower urinary tract / Jonathan Epstein, Tamara L. Lotan -- Female genital system and breast / Lora Hedrick Ellenson, Susan C. Lester -- Endocrine system / Anirban Maitra -- Bones, joints, and soft tissue tumors / Andrew Horvai -- Peripheral nerves and muscles / Peter Pytel -- Central nervous system / Matthew P. Frosch -- Skin / Alexander J.F. Lazar
Includes bibliographical references and index
Keywords: Pathologic Processes; Pathology; Pathology